Developing Offspring Strategy in Manufacturing Industry of Iran : An Empirical Study - Fadaki, Seyed Mohammad Hossein (2010)
This thesis examines an innovative strategy, i.e. offspring strategy and its implications on company\'s performance. Generally, offspring strategy is a tailored made strategy which ventures from outsourcing to insourcing and subsequently spinning off the production line to a new enterprise. This thesis uses multiple case study method to explore the different perspectives of offspring strategy ranging from the formulation to implementation of the strategy and the financial and non-financial implications for companies selected in the study.